Pengaruh Gaya Kepemimpinan dan Lingkungan Kerja terhadap Kinerja Pegawai Melalui Motivasi Kerja Sebagai Variabel Mediasi Pada Sekretariat Daerah Kabupaten Tanjung Jabung Barat - Fahlepi, Riza; Syekh, Saiyid; Sudirman, Sudirman (J-MAS (Jurnal Manajemen dan Sains), 2024)
This study aims to determine and analyze the influence of Leadership Style and work environment on employee performance through work motivation as a mediating variable at the Regional Secretariat of Tanjung Jabung Barat Regency. The type of research uses descriptive and verification research. The object of this study is the employees of the Regional Secretariat of Tanjung Jabung Barat Regency totaling 118 people. This study uses the PLS analysis method. Based on the results of the questionnaire on Leadership Style, namely in the good category. Then for the description of the work environment variable, the category is good. Furthermore, the description of the work motivation variable is in the high category. While the description of the employee performance variable is in the high category. Based on the results of the study, Leadership Style has a positive and significant effect on work motivation. The work environment has a positive and significant effect on work motivation. Leadership style does not have a significant effect on employee performance. Work environment has a positive and significant effect on employee performance. Work motivation has a positive and significant effect on employee performance. Leadership style has a positive and significant effect on employee performance mediated by work motivation. Work environment has a positive and significant effect on employee performance mediated by work motivation at the Regional Secretariat of Tanjung Jabung Barat Regency.